The Catholic Church’s Responsibility in Creating a Safeguarding Culture - Hans Zollner (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The safeguarding of minors and of vulnerable adult persons is an intrinsic aspect of the mission that the Lord has entrusted the Church and it is the responsibility of all the faithful to fulfil it, whatever capacity they hold in the Church. Unfortunately, it is not possible to eradicate child abuse entirely as it is a human reality, but much can be done by creating a culture of safe space and safe relationships within the Church and beyond. The Catholic Church, as the oldest and biggest institution in the world and with its religious and moral values, has a special responsibility in preventing any kind of abuse, in protecting the most vulnerable, and furthermore, in Safeguarding; in creating safe spaces and safe relationships. Listening to victims and survivors of abuse who have been harmed in the Church or outside, is key for being and acting in a responsible, accountable, and transparent way. This is the cornerstone for credibility and for promoting the faith.